Neuro-immune axis in atherosclerosis: mechanisms of regulation and therapeutic opportunities - Shang, Yuxin; Pan, Yuqing; Xie, Lingling; Zhao, Yan; Mao, Wei; Chen, Tingting (Frontiers in Immunology, 2025)
Atherosclerosis, the leading cause of cardiovascular morbidity and mortality worldwide, is now firmly established as a chronic immune-mediated disorder rather than a purely lipid-storage disease. Accumulating evidence has uncovered a previously underappreciated dimension of atherogenesis: the dynamic and bidirectional crosstalk between the nervous and immune systems. This neuroimmune axis, involving intricate communication between autonomic neural circuits and vascular immune cells, plays a central role in regulating arterial inflammation and plaque development. In particular, neuroimmune cardiovascular interfaces (NICIs)—specialized anatomical and functional hubs—have emerged as key sites for signal integration. Here, we review recent mechanistic insights into how sympathetic and parasympathetic pathways influence immune responses in atherosclerotic vessels and hematopoietic organs. We focus on the roles of neuromodulators such as pituitary adenylate cyclase-activating polypeptide (PACAP), calcitonin gene-related peptide (CGRP), neuropeptide Y (NPY), and galanin in shaping myeloid cell behavior, vascular tone, and endothelial activation. Additionally, we examine translational advances in neuromodulatory interventions—ranging from vagus nerve stimulation (VNS) to selective α7 nicotinic acetylcholine receptor (α7nAChR) agonists—that target these pathways to mitigate vascular inflammation in experimental models. These findings suggest that spatially resolved and temporally dynamic neuroimmune interactions constitute a critical layer of regulation in atherogenesis, offering a compelling framework for novel anti-inflammatory therapies beyond traditional lipid-lowering strategies.